Alcohol Intake and Cardiovascular Outcomes in Patients With Atrial Fibrillation: RE‐LY AF Registry Analysis - Alireza Oraii; David Conen; Linda S. Johnson; William F. McIntyre; Faith Kirabo; Kumar Balasubramanian; Alexander P. Benz; Jonas Oldgren; Jens Cosedis Nielsen; Jeff Healey (Annals of Noninvasive Electrocardiology, 2025)
ABSTRACT Background Alcohol intake increases recurrence of atrial fibrillation (AF), but its relationship with cardiovascular outcomes is less well characterized. We aimed to study the association between different levels of alcohol intake and cardiovascular outcomes in a global cohort of patients with AF. Methods This is a cross‐sectional analysis of the RE‐LY AF registry, including 15,400 patients with AF who visited emergency departments in 47 countries. Patients were categorized into abstainers, light (< 7 standard drinks [SD]/week), moderate (7–13 SD/week), and heavy drinkers (≥ 14 SD/week). Outcomes were stroke/systemic embolism, heart failure (HF) hospitalization, and major bleeding at 1‐year follow‐up. Logistic mixed‐effects regression models were used to calculate multivariable‐adjusted odds ratios (aOR) with a 95% confidence interval (CI). Results In total,14,058 patients (mean age = 65.9 ± 14.7 years, 48.0% women) with available alcohol intake level data were included. This consisted of 12,091 (86.0%) abstainers, 1150 (8.2%) light, 458 (3.3%) moderate, and 359 (2.6%) heavy drinkers. The odds of stroke/systemic embolism were not significantly different in light (aOR = 0.88, 95% CI: 0.60–1.28), moderate (aOR = 0.91, 95% CI: 0.53–1.57) or heavy drinkers (aOR = 0.79, 95% CI: 0.41–1.54) compared to abstainers. Major bleedings were numerically, but not statistically significantly, higher among heavy drinkers (aOR = 1.52, 95% CI: 0.82–2.80). Compared to abstainers, alcohol intake was associated with fewer HF hospitalizations (light: aOR = 0.73, 95% CI: 0.58–0.92; moderate: aOR = 0.53, 95% CI: 0.35–0.78; heavy: aOR = 0.63, 95% CI: 0.41–0.98). However, this protective association was observed only in upper‐middle and high‐income countries (p‐interaction < 0.001). Conclusion Alcohol drinking is unlikely to be associated with increased thromboembolic events in patients with AF, but may be associated with a lower risk of HF hospitalizations.